SENIOR FORMS STUDENTS’ COGNITIVE ACTIVITY DEVELOPMENT IN ENGLISH TEXTUAL ACTIVITY - Protasova, N.V. (Tambov University Review. Series: Humanities, 2016)
It is devoted to considering a question of using popular-science texts as the main means of senior forms students’ cognitive activity development. In our work we base on some principles of I. Kant’s theory of knowledge about cognitive activity, and a priori and a posteriori knowledge. We consider a priori knowledge as depending on experience, theoretical, speculative, having universal and necessary indications, developing senior students’ abilities to generalize, to analyze, to compare, to reason, to find decisions in different situations and a posteriori knowledge as practical, depending on experience. Schoolchildren’s a priori and a posteriori knowledge development is possible at usual English practical lessons and also at elective courses, including the popular-science texts into the educational process. Methods of working with popular-science texts have their own distinguishing features. It’s important to acquaint students with the structure of offering texts and specific language means. We come to the conclusion that using popular-science texts at English lessons at school will help to develop the cognitive activity, senior forms students’ a priori and a posteriori knowledge, will better the subject knowledge of science direction and the English language.